Socio-economic analysis on waste pickers in selected municipal solid waste disposal sites in Malaysia / Aida Husna Binti Zahariman - Zahariman, Aida Husna (2015)

(untitled)
Waste production in Malaysia has increased to 30,000 ton per day. It is estimated that 90% of the waste is sent to landfills without any recovery of recyclable materials. This situation provides the waste pickers with a way to make a living by recovering the said materials. The purpose of this study is to understand the socio-economics of the waste pickers in three landfills in Selangor. The three landfills are: a sanitary landfill in Jeram, a non-sanitary landfill in Dengkil, and an open landfill in Bukit Beruntung. Both the Jeram and Dengkil landfills are under the management of Worldwide Holdings, while the Bukit Beruntung landfill is under the management of the Hulu Selangor Municipal Council. The method of this study involves the observation of and distribution of survey forms among waste pickers. The result of the study indicates that the majority of the waste pickers on all three landfills are men. In both Jeram and Dengkil, 100% of the waste pickers are Indonesians. In Bukit Beruntung however, 83.3% of the waste pickers, which is the majority, are Malaysians. In terms of level of education, it is discovered that 86.7% waste pickers in Jeram, and 66.7% waste pickers in Dengkil only completed elementary education. On the other hand, in Bukit Beruntung, 56.7% of the waste pickers completed at least lower secondary education. Driven by the lack of job opportunity and the relatively lucrative income that can be derived from waste picking, nearly all of the waste pickers in Jeram and Dengkil chose to become full time waste pickers with percentages of 90% and 100% respectively. The situation is slightly different in Bukit Beruntung, where only 40% of the waste pickers chose to work as full time waste pickers in the landfill. In terms of income, waste picking activity is capable of generating over RM1000 per month. Some respondents have also had the history of illnesses like dizziness, fever, body ache, respiratory problems and chronic diseases. From the study conducted, it can be concluded that despite the numerous challenges faced by the workers, they persevere and continue to perform their jobs. The main motivation behind this perseverance is financial rather than the love of the environment.